Topology Optimization of an aircraft engine gearbox - Nuz Wattananaphakaseam; Natthasit Sittisang; Napat Phengsalae; Daniele Dipasquale (My University, 2021)
Abstract Topology Optimization (TO) is a mathematical method extensively employed to optimize material layout within the design space, for a given set of boundary conditions with the goal of maximizing the performance of the system. This process takes a three-dimensional design space and whittles material away within it to achieve the most efficient design. Currently, engineers use this mathematical approach at a concept level of a design process, leading to results which are often fine-tuned for manufacturability. In some cases, the optimized geometry can be directly manufactured using additive manufacturing, indeed, TO is a key part of design for additive manufacturing. This work aims to apply TO in order to minimize the mass of an engine gearbox while maintaining an acceptable mechanical performance when compared to the original design. Numerical simulations are carried out by means of CAD and FEM software in order to improve the design of an aircraft gearbox composed of four gears, therefore, irrelevant parts of material are removed in the design space to meet the goal of minimizing the mass of the gearbox. The application of TO allows to obtain a better, lighter, and more efficient design of the gearbox by keeping its mechanical performance unchanged.
Keywords: Topology optimization; Topology Optimization in Engineering